Rappresentazione del potere e potere della rappresentazione. Ritratti di giudici - Campanale, Anna Maria (Cultura giuridica e diritto vivente, 2018)
[The Representation of Power and the Power of Representation. Judicial portraiture] Marin’s semiology describes a chiasmus: the power of representation and the representation of power. This chiasmus reveals the indissoluble relationship between power and representation and offers a theoretical reflection on the politics of images. In this perspective, this paper suggests the interpretation of portraits of judges as representation of judicial power and, ultimately, of Justice. Judicial portraiture shows, prima facie, pictures of judges emphasized by the solemnity of their robes and wigs: however, what emerges from the portraits is the personification of Justice. But the image is polysemious, because spectators are implicated in representation. In The Trial by Kafka, a powerful example is the transfiguration of the Goddess of Justice into the Goddess of the Hunt in K.’s eyes, while painter Titorelli draws the allegorical figure - Justice and the Goddess of Victory at the same time - behind the judge’s throne.